7.3 Solutions 323
The frequency equation is obtained by equating to zero the determinant
formed by the coefficients of A, B and C
(k −mω
2
) −k 0
−k (2k − Mω
2
) −k
0 −k (k − mω
2
)
= 0
Expanding the determinant we obtain
ω
2
(k −mω
2
)(ω
2
Mm − 2km − Mk) = 0 (13)
The frequencies are
ω
1
= 0,ω
2
=
k
m
,ω
3
=
k(2m + M)
Mm
(14)
The frequency ω
1
= 0 simply means a translation of all the three particles
without vibration. Ratios of amplitudes of the three particles can be found out
by substituting ω
2
and ω
3
in (10), (11) and (12). Thus when ω = ω
2
k
m
is
substituted in (10), we find the amplitude for the central atom B = 0. When
B = 0 is used in (11) we obtain C =−A. This mode of oscillation is depicted
in Fig. 7.27a.
Fig. 7.27
Substituting ω = ω
3
=
k(2m + M)
Mm
in (10) and (12) yields
B =−
2m
M
A =−
2m
M
C
Thus in this mode particles of mass m oscillate in phase with equal amplitude
but out of phase with the central particle.
This problem has a bearing on the vibrations of linear molecules such as
CO
2
. The middle particle represents the C atom and the particles on either side
represent O atoms. Here too there will be three modes of oscillations. One will
have a zero frequency, ω
1
= 0, and will correspond to a simple translation
of the centre of mass. In Fig. 7.27a the mode with ω
1
= ω
2
is such that the
carbon atom is stationary, the oxygen atoms oscillating back and forth in oppo-
site phase with equal amplitude. In the third mode which has frequency ω
3
,
the carbon atom undergoes motion with respect to the centre of mass and is
in opposite phase from that of the two oxygen atoms. Of these two modes